Coupling effects between pantograph of high-speed train and tunnel. Issue 11 (2nd November 2022) - Ji, Zhanling; Guo, Yi; Guo, Dilong; Yang, Guowei; Zhang, Lingfang
Abstract : Compression and expansion waves are generated as a train enters a tunnel at high speed. The waves ceaselessly pass through a pantograph as they propagate back and forth in the tunnel; air flow sharply jumps at the exit of the tunnel. The interaction between the pantograph and its surrounding air is significant. In this study, a precise and highly efficient coupling method between aerodynamics and multi-body dynamics was developed. The proposed method was verified using line test data. Comparative analyses were conducted between open-air coupling and tunnel coupling, with coupled or non-coupled aerodynamics and multi-body dynamics passing through a tunnel. Some coupling characteristics in time and frequency domains, such as the aerodynamic lift of the panhead, the contact force between pantograph and catenary, and the vertical displacement and acceleration of contact strip, were investigated to clarify the dynamic coupling behaviours and characteristic evolution laws of the pantograph, as well as the coupling effect between the pantograph and tunnel. The results of this work may provide a sound theoretical basis for further improving the current collection quality from the source.